2004
DOI: 10.1002/jcb.20019
|View full text |Cite
|
Sign up to set email alerts
|

Distinct functions of BMP4 and GDF5 in the regulation of chondrogenesis

Abstract: Bone morphogenetic protein 4 (BMP4) and growth/differentiation factor 5 (GDF5) are closely related protein family members and regulate early cartilage patterning and differentiation. In this study, we compared the functional outcome of their actions systematically at various stages of chondrogenesis in mouse embryonic limb bud mesenchyme grown in micromass cultures. Overall, both growth factors enhanced cartilage growth and differentiation in these cultures. Uniquely, BMP4 not only accelerated the formation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
126
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 145 publications
(132 citation statements)
references
References 65 publications
(81 reference statements)
5
126
1
Order By: Relevance
“…MDSCs have previously been shown to have chondrogenic potential (24,25), especially after BMP-4 transduction. BMP-4 has also been demonstrated to enhance potential for chondrogenesis in vitro and in vivo in cell types other than MDSCs (38)(39)(40). It has also been reported that the combined effect of TGF␤3 and BMP-4 or BMP-2 on chondrogenic pellet size is greater than that of each growth factor administered separately (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…MDSCs have previously been shown to have chondrogenic potential (24,25), especially after BMP-4 transduction. BMP-4 has also been demonstrated to enhance potential for chondrogenesis in vitro and in vivo in cell types other than MDSCs (38)(39)(40). It has also been reported that the combined effect of TGF␤3 and BMP-4 or BMP-2 on chondrogenic pellet size is greater than that of each growth factor administered separately (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…Significant association of polymorphism in GDF-5 with KOA could be related to role of variant T allele to influence transcription of the GDF5 gene with the susceptible allele showing reduced transcriptional activity (Miyamoto et al, 2007). The reduced activity of GDF5 may inhibit the process of early cartilage differentiation (Hatakeyama et al, 2004). Genetic variations in the GDF5 locus have been reported to be involved in the pathogenesis of rheumatoid arthritis and to influence human height, hip axis length and fracture risk in the elderly (Rouault et al, 2010;Vaes et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Growth and differentiation factor 5 (GDF-5), also known as cartilage derived morphogenetic protein of Transforming Growth Factor-b (TGF-b) superfamily, plays an important role in the development, maintenance and repair of bone and cartilage. It has been shown that reduced transcriptional activity leads to decrease in cartilage synthesis (Francis-West et al, 1999;Hatakeyama et al, 2004;Southam et al, 2007) and to compensate for the cartilage space, the bone beneath thickens and spreads out form knobbly outgrowths (osteophytes).…”
Section: Mmp-14 Mt1-mmp)mentioning
confidence: 99%
“…While a role for GDF-7/BMP-12 in chondrocyte biology and growth plate kinetics has, to our knowledge, not been reported in the literature, there is extensive evidence implicating the related molecule, GDF-5, in chondrocyte differentiation and maturation. [1][2][3][4][5][6][7] Most recently, 5-week-old female mice deficient in GDF-5 were shown to have the opposite phenotype in the proximal tibial growth plate relative to that seen in the present study with GDF-7 deficient mice of the same age and sex. 8 Compared to control growth plates, the physes from GDF-5 À/À animals had slower growth rates that were associated with a longer hypertrophic phase duration, whereas, in our current study, GDF-7 deficient growth plates had faster growth rates that were associated with a shorter hypertrophic phase duration.…”
Section: Discussionmentioning
confidence: 57%
“…[1][2][3][4][5][6][7] Five-week-old female mice deficient in one of these molecules, GDF-5, have additionally been shown to exhibit a significant reduction in proximal tibial growth rate due to a lengthened hypertrophic phase duration. 8 Most recently, Miyamoto and colleagues have demonstrated that Gdf5 appears to be a susceptibility gene for osteoarthritis, and that decreased Gdf5 expression may be associated with the development of this degenerative joint disease.…”
mentioning
confidence: 99%